USM IN SMART PARTNERSHIP WITH CIDB - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 27 October 2015 – Universiti Sains Malaysia (USM) had forged a smart partnership with the Construction Industry Development Board (CIDB) to provide cooperation and support in implementing the Malaysian Construction Industry Transformation Programme (CITP), as affirmed in the CITP Pledgesigning Ceremony, together with the industry leaders at the Sime Darby Convention Centre recently.